Fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film and preparation method thereof

By blending fluorenol polyester and polyaryletherurea, the conjugated structure is destroyed and leakage loss is reduced, and the problem of low charge and discharge efficiency of existing polymer capacitors at high temperatures is solved, and excellent dielectric energy storage performance is achieved at high temperatures and high fields.

CN120157928APending Publication Date: 2025-06-17HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510304695.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

Existing polymer capacitors have high leakage loss and low charge and discharge efficiency at high temperatures, which cannot meet the needs of high temperature applications in aerospace, hybrid vehicles and other fields.

Method used

By blending fluorene polyester with polyaryletherurea, the conjugated structure in the fluorene polyester matrix is ​​destroyed, leakage loss is reduced, and the high-temperature dielectric energy storage performance of the film is improved through the regulation and control process.

Benefits of technology

It significantly improves the charge and discharge efficiency and high discharge energy density of polymers at high temperatures and high fields, reduces dielectric loss, and improves the high-temperature dielectric energy storage performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120157928A_ABST
    Figure CN120157928A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of dielectric materials and dielectric energy storage, and particularly relates to a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film and a preparation method thereof. The preparation method specifically comprises the following steps: adding fluorene polyester and polyaryletherurea into a solvent, fully dissolving to obtain a mixed solution, uniformly coating a substrate with the mixed solution, and then drying; and carrying out vacuum annealing on the dried film, and then carrying out curing treatment to strip the film from the substrate to obtain the fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film, thereby improving the charge-discharge efficiency and high discharge energy density of the polymer under high temperature and high field, and solving the problems of high electric leakage loss and low cost of the existing polymer film. And the charging and discharging efficiency is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of dielectric materials and dielectric energy storage, and particularly relates to a fluorene polyester and poly(aryl ether urea) blended dielectric energy storage polymer film and a preparation method thereof. Background Art

[0002] Polymer dielectrics with light weight, low cost, and easy large-scale processing have the advantages of high breakdown field strength and high power density, and are widely used in energy storage capacitors. Currently, in the fields of aerospace, hybrid vehicles, oil and gas exploration, etc., it is required that polymer capacitors can work at relatively high temperatures (>150 °C). However, the highest working temperature of the biaxially oriented polypropylene (BOPP) used in existing commercial capacitors is 105 °C, which cannot meet the high-temperature application requirements. Therefore, there is an urgent need to develop high-temperature polymer-based energy storage dielectric materials.

[0003] Among many polymers, polymers with high glass transition temperatures have become a research hotspot for current high-temperature polymer dielectric materials due to their good thermal stability. Among them, fluorene polyester (FPE) is a high-temperature polymer widely used in engineering fields such as insulation and energy storage. Fluorene polyester has an extremely high glass transition temperature (320 °C) and a dielectric loss below 0.003 in the range of 25 - 250 °C. However, at high temperatures and high fields, due to the conjugated structure in fluorene polyester, the leakage current loss increases sharply and the charge-discharge efficiency drops significantly, severely limiting the application of fluorene polyester in the field of high-temperature dielectric energy storage. By doping inorganic nanoparticles or organic semiconductor fillers with high band gaps, the polymer conductivity can be effectively inhibited, the breakdown strength can be increased, and thus the high-temperature dielectric energy storage performance can be improved. However, the method of nanocomposite often leads to non-uniform energy storage performance of the material, limiting the possibility of its large-scale application. Therefore, it is crucial to explore new polymer modification schemes to improve the high-temperature and high-field energy storage performance of polymers. Summary of the Invention

[0004] In view of the above defects or improvement requirements of the prior art, the present invention provides a fluorene polyester and poly(aryl ether urea) blended dielectric energy storage polymer film and a preparation method thereof, aiming to improve the charge-discharge efficiency and high discharge energy density of the polymer under high temperature and high field by blending fluorene polyester and poly(aryl ether urea), thereby solving the technical problems of high leakage current loss and low charge-discharge efficiency existing in the prior art.

[0005] To achieve the above object, according to one aspect of the present invention, a preparation method of a fluorene polyester and poly(aryl ether urea) blended dielectric energy storage polymer film is provided, including the following steps:

[0006] (1) Add fluorene polyester and poly(aryl ether urea) into a solvent, fully dissolve to obtain a mixed solution, uniformly coat the mixed solution on a substrate, and then dry it.

[0007] (2) Vacuum anneal the dried film in step (1), and then perform a curing treatment to peel the film from the substrate, thereby obtaining a blended dielectric energy storage polymer film of fluorene polyester and poly(aryl ether urea).

[0008] Preferably, in step (1), the mass ratio of the poly(aryl ether urea) to the mass of the fluorene polyester is 0.05 - 0.5.

[0009] Preferably, the ratio of the sum of the masses of fluorene polyester and poly(aryl ether urea) in the mixed solution to the volume of the solvent is 20 - 60 mg / mL.

[0010] Preferably, the organic solvent is one or both of N,N-dimethylformamide or N-methylpyrrolidone.

[0011] Preferably, in step (1), the dissolution conditions are stirring for 8 - 12 h under heating at 35 - 50 °C.

[0012] Preferably, in step (1), the drying is specifically as follows: first preheat at 30 - 50 °C for 20 - 60 min, and then dry at 80 - 200 °C for 8 - 12 h.

[0013] Preferably, the annealing temperature is 150 - 200 °C, and the annealing time is 8 - 12 h.

[0014] Preferably, the curing treatment is specifically to immerse the annealed film in deionized water.

[0015] Preferably, after taking out the film immersed in deionized water, dry it to remove water. The temperature for drying and removing water is 40 - 60 °C, and the time is 1 - 4 h.

[0016] According to another aspect of the present invention, there is provided a blended dielectric energy storage polymer film of fluorene polyester and poly(aryl ether urea) prepared by the preparation method described above.

[0017] Generally speaking, compared with the prior art through the above technical solutions conceived by the present invention, the following main advantages are mainly possessed:

[0018] 1. In the present invention, poly(aryl ether urea) (PEEU) with strong polarity and high glass transition temperature (greater than 250 °C) is introduced into the fluorene polyester (FPE) matrix by a blending method, inducing the interaction between groups on the molecular chain, thereby destroying the original conjugated structure in the fluorene polyester matrix. This spatially distorted and distorted molecular chain structure effectively reduces the leakage loss and increases the breakdown field strength, which helps to improve the charge-discharge efficiency and high discharge energy density of the polymer under high temperature and high field. At the same time, due to the strong polarity of PEEU (dielectric constant is 4.7), the dielectric constant of the blended polymer reaches 4.5, which is higher than the dielectric constant of FPE (dielectric constant is 3.3), helping to improve the high-temperature dielectric energy storage performance of the polymer film.

[0019] 2. By regulating the time and temperature of preheating and drying, and controlling the dosage ratio of fluorene polyester, polyaryletherurea and solvent, the prepared blend dielectric energy storage polymer film of fluorene polyester and polyaryletherurea has a flat surface, uniform high-temperature and high-field energy storage performance, stable dielectric constant and low dielectric loss in a wide temperature range. Therefore, the film prepared by the present invention has important application prospects in the field of high-temperature dielectric energy storage; the preparation of the blend polymer film of fluorene polyester / polyaryletherurea in the present invention is by solution casting method, which is simple to operate and has the application potential of large-scale production.

[0020] 3. The blend polymer film of fluorene polyester / polyaryletherurea prepared by the present invention exhibits excellent high-temperature dielectric energy storage performance. At 150 °C, the film achieves a discharge energy density of 9.48 J / cm 3 while maintaining a charge-discharge efficiency of more than 90%; when maintaining a charge-discharge efficiency of more than 90% at 200 °C, the discharge energy density reaches 8.18 J / cm 3 , which is much higher than that of the matrix polymer FPE (the discharge energy density is 1.40 J / cm 3 at 150 °C and 0.86 J / cm 3 at 200 °C). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic flow chart of a method for preparing a blend dielectric energy storage polymer film of fluorene polyester and polyaryletherurea provided by the present invention.

[0022] Figure 2 is a schematic molecular structure diagram of fluorene polyester and polyaryletherurea used in the present invention; where a is fluorene polyester and b is polyaryletherurea.

[0023] Figure 3 is the dielectric spectrum at room temperature of Examples 1-5 and Comparative Examples 1-2 of the present invention; where a is the dielectric constant diagram and b is the dielectric loss diagram.

[0024] Figure 4 is the temperature-variable dielectric diagram of Example 2 and Comparative Examples 1-2 of the present invention in the temperature range of 25-250 °C, where the frequency is fixed at 1000 Hz.

[0025] Figure 5 is the energy storage performance diagram at 150 °C of Examples 1-5 and Comparative Examples 1-4 of the present invention; where a is the discharge energy density diagram and b is the charge-discharge efficiency diagram.

[0026] Figure 6 is the Weibull distribution diagram of the DC breakdown field strength at 150 °C of Example 2 and Comparative Examples 1-4 of the present invention.

[0027] Figure 7 This is the energy storage performance graph of Example 2 of the present invention and Comparative Examples 1 to 4 at 200 °C.

[0028] Figure 8 This is the Weibull distribution graph of the DC breakdown field strength of Example 2 of the present invention and Comparative Examples 1 to 4 at 200 °C. Detailed implementation manners

[0029] In order to make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] Example 1

[0031] A blend dielectric energy storage polymer film of fluorene polyester and poly(aryl ether urea) (mass ratio of PEEU / FPE is 0.05) is prepared by the following steps:

[0032] Weigh 0.2 g of FPE powder and 0.01 g of PEEU powder (the structural formula is as Figure 2 shown) and dissolve them in 5 mL of DMF solvent to prepare a polymer solution with a concentration of 42 mg / mL. Stir magnetically at a rate of 400 rpm / min at 50 °C for 8 h, and then measure an appropriate amount of the solution and cast it on a glass plate to form a film. The sample is first preheated in an oven at 40 °C for 30 min, then the oven temperature is adjusted, and the solvent is dried by a process of keeping warm at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cooled to room temperature with the furnace. Place the glass plate with the sample in a vacuum oven and anneal it at 200 °C in vacuum for 12 h. After cooling to room temperature, soak the film in deionized water. After the film is peeled off, place it in an oven and dry it at 50 °C to obtain a blend dielectric energy storage polymer film of fluorene polyester and poly(aryl ether urea) with a thickness of 12 μm.

[0033] Example 2

[0034] A blend dielectric energy storage polymer film of fluorene polyester and poly(aryl ether urea) (mass ratio of PEEU / FPE is 0.1) is prepared by the following steps:

[0035] Weigh 0.2 g of FPE powder and 0.02 g of PEEU powder, dissolve them in 5 mL of DMF solvent to prepare a polymer solution with a concentration of 44 mg / mL. Stir magnetically at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. First, place the sample in an oven preheated at 40 °C for 30 min, adjust the oven temperature, and dry the solvent by the process of maintaining at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cool it to room temperature with the furnace. Place the glass plate with the sample in a vacuum oven, perform vacuum annealing at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film is peeled off, place it in an oven and dry it at 50 °C to obtain a fluorene polyester and poly(aryl ether urea) blend dielectric energy storage polymer film with a thickness of 12 μm.

[0036] Example 3

[0037] A fluorene polyester and poly(aryl ether urea) blend dielectric energy storage polymer film (the mass ratio of PEEU / FPE is 0.2) is prepared by the following steps:

[0038] Weigh 0.2 g of FPE powder and 0.04 g of PEEU powder, dissolve them in 5 mL of DMF solvent to prepare a polymer solution with a concentration of 48 mg / mL. Stir magnetically at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. First, place the sample in an oven preheated at 40 °C for 30 min, adjust the oven temperature, and dry the solvent by the process of maintaining at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cool it to room temperature with the furnace. Place the glass plate with the sample in a vacuum oven, perform vacuum annealing at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film is peeled off, place it in an oven and dry it at 50 °C to obtain a fluorene polyester and poly(aryl ether urea) blend dielectric energy storage polymer film with a thickness of 12 μm.

[0039] Example 4

[0040] A fluorene polyester and poly(aryl ether urea) blend dielectric energy storage polymer film (the mass ratio of PEEU / FPE is 0.3) is prepared by the following steps:

[0041] Weigh 0.2 g of FPE powder and 0.06 g of PEEU powder and dissolve them in 5 mL of DMF solvent to prepare a polymer solution with a concentration of 52 mg / mL. Stir magnetically at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. First, place the sample in an oven preheated at 40 °C for 30 min. Adjust the oven temperature and dry the solvent by the process of maintaining at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cool it to room temperature with the furnace. Place the glass plate with the sample in a vacuum oven and anneal it under vacuum at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film peels off, place it in an oven and dry it at 50 °C to obtain a fluorene polyester and poly(aryl ether urea) blended dielectric energy storage polymer film with a thickness of 12 μm.

[0042] Example 5

[0043] A fluorene polyester and poly(aryl ether urea) blended dielectric energy storage polymer film (mass ratio of PEEU / FPE is 0.5) is prepared by the following steps:

[0044] Weigh 0.2 g of FPE powder and 0.1 g of PEEU powder and dissolve them in 5 mL of DMF solvent to prepare a polymer solution with a concentration of 60 mg / mL. Stir magnetically at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. First, place the sample in an oven preheated at 40 °C for 30 min. Adjust the oven temperature and dry the solvent by the process of maintaining at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cool it to room temperature with the furnace. Place the glass plate with the sample in a vacuum oven and anneal it under vacuum at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film peels off, place it in an oven and dry it at 50 °C to obtain a fluorene polyester and poly(aryl ether urea) blended dielectric energy storage polymer film with a thickness of 12 μm.

[0045] Comparative Example 1

[0046] A fluorene polyester (FPE) film is prepared by the following steps:

[0047] Weigh 0.2 g of FPE powder and dissolve it in 5 mL of DMF solvent to prepare a polymer solution with a concentration of 40 mg / mL. Stir magnetically at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. The sample is first preheated in an oven at 40 °C for 30 min, then the oven temperature is adjusted, and the solvent is dried by a process of maintaining at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cooled to room temperature in the furnace. Place the glass plate with the sample in a vacuum oven and anneal it under vacuum at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film is peeled off, place it in an oven and dry it at 50 °C to obtain an FPE film with a thickness of 12 μm.

[0048] Comparative Example 2

[0049] A poly(aryl ether urea) (PEEU) film is prepared by the following steps:

[0050] Weigh 0.2 g of PEEU powder and dissolve it in 5 mL of DMF solvent to prepare a polymer solution with a concentration of 40 mg / mL. Stir magnetically at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. The sample is first preheated in an oven at 40 °C for 30 min, then the oven temperature is adjusted, and the solvent is dried by a process of maintaining at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cooled to room temperature in the furnace. Place the glass plate with the sample in a vacuum oven and anneal it under vacuum at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film is peeled off, place it in an oven and dry it at 50 °C to obtain a PEEU film with a thickness of 12 μm.

[0051] Comparative Example 3

[0052] A dielectric energy storage polymer film obtained by blending fluorene polyester and polyetherimide (the mass ratio of polyetherimide / fluorene polyester is 0.1) is prepared by the following steps:

[0053] Weigh 0.2 g of FPE powder and 0.02 g of polyetherimide powder and dissolve them in 5 mL of NMP solvent to prepare a polymer solution with a concentration of 44 mg / mL. Magnetically stir the solution at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. First, place the sample in an oven preheated to 40 °C for 30 min. Adjust the oven temperature and dry the solvent using a process of holding at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cool it to room temperature with the furnace. Place the glass plate with the sample in a vacuum oven and perform vacuum annealing at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film peels off, place it in an oven and dry it at 50 °C to obtain a fluorene polyester and polyetherimide blended dielectric energy storage polymer film with a thickness of 12 μm.

[0054] Comparative Example 4

[0055] A polyaryletherurea and polyimide blended dielectric energy storage polymer film (the mass ratio of polyaryletherurea / polyimide is 0.1) is prepared by the following steps:

[0056] Weigh 0.2 g of polyimide powder and 0.02 g of polyaryletherurea powder and dissolve them in 5 mL of NMP solvent to prepare a polymer solution with a concentration of 44 mg / mL. Magnetically stir the solution at a rate of 400 rpm / min at 50 °C for 8 h. Then, measure an appropriate amount of the solution and cast it on a glass plate to form a film. First, place the sample in an oven preheated to 40 °C for 30 min. Adjust the oven temperature and dry the solvent using a process of holding at 80 °C for 8 h, 125 °C for 1 h, 150 °C for 1 h, 175 °C for 1 h, and 200 °C for 1 h, and then cool it to room temperature with the furnace. Place the glass plate with the sample in a vacuum oven and perform vacuum annealing at 200 °C for 12 h. After cooling to room temperature, immerse the film in deionized water. After the film peels off, place it in an oven and dry it at 50 °C to obtain a polyaryletherurea and polyimide blended dielectric energy storage polymer film with a thickness of 12 μm.

[0057] Test results:

[0058] Figure 3 Fig. is the room temperature dielectric spectra of Examples 1 - 5 and Comparative Examples 1 - 2. Examples 1 - 5 have relatively high dielectric constants (4 - 4.6), which are better than that of Comparative Example 1 (FPE), and the loss shows no obvious change, remaining below 0.025.

[0059] Figure 4 Fig. is the temperature-dependent dielectric spectra of Example 2 and Comparative Examples 1 - 2. Example 2 has stable dielectric constants and low dielectric losses within the range of 25 - 250 °C, and its dielectric properties have excellent temperature stability.

[0060] Figure 5Energy storage performance graphs of Examples 1-5 and Comparative Examples 1-4 at 150 °C. The high-temperature energy storage performance of Example 2 is significantly better than that of Comparative Examples 1-4, especially the energy storage performance data with a charge-discharge efficiency of over 90%. At 150 °C and 700 MV / m, Example 2 has an ultra-high discharge energy density of 9.48 J / cm 3 (efficiency greater than 90%), which is 7 times that of Comparative Example 1 (1.40 J / cm 3 ), and still has an efficiency of 86% and a discharge energy density of 10.71 J / cm 3 at 750 MV / m.

[0061] Figure 6 The Weibull distribution graph of the DC breakdown field strength of Example 2 and Comparative Examples 1-4 at 150 °C. The specific formula is as follows:

[0062] P(E) = 1 - exp(-(E b / α) β )

[0063] where P(E) is the cumulative probability of electrical breakdown, E b is the experimentally measured electric field strength, the parameter α is the breakdown field strength at a cumulative breakdown probability of 63% for the sample, and the parameter β can be used to judge the dispersion of the data. An increase in the β value indicates a low degree of dispersion and high reliability of the breakdown data. The DC breakdown strength of Example 2 is 780 MV / m, which is 50% and 80% higher than 512 MV / m of Comparative Example 1 and 435 MV / m of Comparative Example 2 respectively, indicating that the introduction of PEEU effectively increases the polymer breakdown field strength and improves the high-temperature insulation performance.

[0064] Figure 7 Energy storage performance graphs of Example 2 and Comparative Examples 1-4 at 200 °C. Example 2 has better high-temperature energy storage performance than Comparative Examples 1-4. At an electric field strength of 650 MV / m, the blend polymer film has a discharge energy density of 8.18 J / cm 3 (charge-discharge efficiency is 91%), which is 9.6 times that of Comparative Example 1 (0.85 J / cm 3 ).

[0065] Figure 8It is the Weibull distribution diagram of the DC breakdown field strength at 200 °C in Example 2 and Comparative Examples 1 to 4. An increase in the β value indicates a low degree of dispersion of the breakdown data and high reliability. The DC breakdown strength of Example 2 is 735 MV / m, which is increased by 80% and 90% respectively compared with 406 MV / m of Comparative Example 1 and 392 MV / m of Comparative Example 2. This shows that Example 2 still maintains excellent insulation performance at 200 °C and is an ideal candidate material for high-temperature energy storage capacitors. It is easy for those skilled in the art to understand that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film, characterized in that: The steps include: (1) adding fluorene polyester and polyaryletherurea into a solvent, fully dissolving to obtain a mixed solution, uniformly coating the mixed solution on a substrate, and then drying; (2) vacuum annealing the dried film in step (1), and then curing the film to peel it off from the substrate, thereby obtaining a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film.

2. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 1, characterized in that: In step (1), the ratio of the mass of the polyaryletherurea to the mass of the fluorene polyester is 0.05 to 0.

5.

3. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 2, characterized in that: The ratio of the sum of the masses of the fluorene polyester and the polyaryletherurea in the mixed solution to the volume of the solvent is 20-60 mg / mL.

4. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 1, characterized in that: The organic solvent is one or both of N,N-dimethylformamide and N-methylpyrrolidone.

5. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 1, characterized in that: In step (1), the dissolution condition is stirring at 35-50° C. for 8-12 hours.

6. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 1, characterized in that: In step (1), the drying is specifically as follows: preheating at 30-50°C for 20-60 minutes, and then drying at 80-200°C for 8-12 hours.

7. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 1, characterized in that: The annealing temperature is 150-200° C., and the annealing time is 8-12 hours.

8. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 1, characterized in that: The curing treatment is specifically to immerse the annealed film in deionized water.

9. The method for preparing a fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film according to claim 8, characterized in that: The membrane immersed in deionized water is taken out and dried to remove water. The drying and dehydration temperature is 40 to 60° C. and the time is 1 to 4 hours.

10. The fluorene polyester and polyaryletherurea blended dielectric energy storage polymer film prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • All-organic composite material as well as preparation method and application thereof

    CN121343333A

  • All-organic composite material and preparation method and application thereof

    CN121343333B

  • Preparation method of all-organic micromolecule composite polymer film and product

    CN121378825A